ANALISA PERUBAHAN PENUTUPAN LAHAN PADA KAWASAN HUTAN LINDUNG GUNUNG NANING KABUPATEN SEKADAU PROVINSI KALIMANTAN BARAT - fauzi, ryo muhammad; Nugroho, Joko; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2016)
Land cover in very important in maintaining the ecological, economic, social, cultural balance as well as science and technology in aregion. Ia an effort to provide necessary data and information, that is fast, complete, valid and actual, it can be done using remote sensing technology and Geographical Information Systems using more than one source image data with different time series.the purpose of this research is to: reveal the condition and land cover changes between 2002 and 2013. The method used in this research was supervised classification with Maximum likelihood and visual, field inspections and spatial analysis with an overlay technique on both the result data interceptions of Citra Satelit Landsat 7 ETM + coverage of 2002 and 2013. The result showed that the area of Gunung Naning Protected Forest in 2002 and 2013 had four classes of land cover namely Primary Dryland Forest Mixed-shrub Agricultural dryland, Shrublands, and Settlements. The result of the analysis of changes in land cover as follows: the Primary Dryland Forest decreased in surface area of 1283.08 ha or 4.85%, Mixed-shrub Agricultural dryland had an increased area of 783.02 ha or by 22.76%, Shrubland had the addition of an 4.64 ha or by 16.78%. The land cover in 2013 was dominated by Primary Dryland Forest i.e of ± 25,150.46 ha or ± 60.88 %while the land cover in the form of settlement has the smallest area i.e, of ± 32.29 ha or ± 0.08%. Keyword : Citra Landsat 7 ETM+, Gunung Naning Protected Forest, Land Cover, West Kalimantan